A case report of a large intracardiac thrombus in a COVID-19 patient managed with percutaneous thrombectomy and right ventricular mechanical circulatory support. Issue 6 (5th November 2020) - Kaki, Amir; Singh, Hemindermeet; Cohen, Gerald; Schreiber, Theodore
Abstract: Background: The coronavirus disease 2019 (COVID-19) has caused a global pandemic with an unprecedented burden on health and the economy worldwide. Although it primarily involves the respiratory tract system, cardiovascular complications, particularly arterial and venous thrombosis, are frequently reported and are associated with adverse outcomes. Case summary: We describe the case of a 57-year-old female who presented with acute hypoxic respiratory failure and shock. She was found to have left lower extremity deep vein thrombosis and a suspected pulmonary embolism. A large mobile right atrial mass was found on echocardiogram. Given the large thrombus burden that portended an extremely high risk for embolization to the pulmonary arteries, emergent percutaneous aspiration of an organized thrombus (rather than thrombolysis) was performed using the AngioVac system (Angiodynamics Inc., Latham, NY, USA) complicated by haemodynamic collapse due to acute right ventricular failure. An Impella RP (Abiomed, Danvers, MA, USA) was then placed, with rapid stabilization of haemodynamics. The patient tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). She was treated with antimicrobial and systemic anticoagulation therapy. She was successfully weaned off the Impella RP on post-operative day 4 and was extubated on day 5. She was discharged on day 16 in a stable condition. Discussion: Incident venous thrombo-embolism is frequently encountered in COVID-19 patients. We report the first case of a large intracardiac thrombus associated with SARS-CoV-2 infection managed successfully with percutaneous thrombectomy and right ventricular mechanical circulatory support.